The Impact of Repeated and Dialogic Reading Strategies on the Development of Palestinian Arabic-Speaking Children's Vocabulary: An Analysis of Receptive, Productive, Mental, and General Words - Найла Таллас-Махайна; Дуа Ельхія; Аредж Хашем Массарве (Психолінгвістика, 2025)
Aim. This study investigates the impact of repeated and dialogic reading strategies on vocabulary development in Palestinian Arabic-speaking children, focusing on receptive and productive vocabulary across different word types (mental vs. general, (Mental words refer to abstract vocabulary, while general words are more concrete)) and age groups: OLDER (n = 27, mean age = 66.2 months) and YOUNGER (n = 38, mean age = 55.1 months).